(untitled) (Literary Voice, 2024)
The paper attempts to explore the women characters of Amish Tripathi in his Shiva Trilogy and Ram Chandra Series with a post-feminist perspective. In the recent trend of mythological fiction, women characters are given the roles of protagonists for voicing their emotions and decisions. From their shadowed existence to their new avatar of prominence and strength they have become role models for the young generation. Tripathi has subverted the characterization of women with extraordinary virtues. His Sita is the pride of Malayputras who confer on her the coveted title of ‘Vishnu’ for making her accountable for the welfare of the people by destroying evil. He very carefully associates masculine qualities with women to prove their wisdom and power. The paper focuses on Tripathi’s defiance of patriarchal society by presenting a world of women who possess masculine qualities along with utmost femininity.